Classification of 4448 Diseases in Siddha System of Medicine – A Review - Rakulini, R. (Journal of Complementary and Alternative Medical Research, 2020)
Introduction: Siddha Medicine is a system of Traditional Medicine originating in ancient Sri Lanka and Tamil Nadu in South India. Traditionally, it is taught the siddhars laid the foundation for this system of Medication. Agastyar is considered the first Siddhar and the guru of all siddhars. Siddha system considers the human body as a collection of tri-humors & seven basic elements. Vatham, Pitham & Kapham are the tri-humors which are the life constituents of the human body. The equilibrium of humors is consider as health & its disturbance or imbalance leads to disease. Aim and Objective: The aim of the study is to identify the 4448 diseases according to the Siddha Literatures. Results and Discussion: 4448 diseases are mentioned in Agasthiyar 2000, Angathipatham, Noi Naadal Noi Muthal Naadal part I and Theriyar vaakadam. Siddhar Aruvai Maruthuvam book stated that Head and neck diseases are 1008. Diseases are classified according to anatomical structures of body parts, tri humors and diseases. Totally, 93 diseases are explained in all five books. In Noi Naadal Noi Muthal Naadal Part II, 51 diseases and its types and In Yugi Vaiththiya Sinthamani, 27 diseases and its types are explained in the books. Totally, 544 and 431 Number of diseases are explained in the text Noi Naadal Noi Muthal Naadal Part II and Yugi Vaiththiya Sinthamani respectively.
Keywords: 4448 diseases; Siddha medicine; Siddha pathology